Adolescentes em "liberdade assistida" : narrativas de (re)encontros com a escola - Siqueira, Luziane de Assis Ruela (2016)
This research investigates the experiences of adolescents serving their socioeducational measures through assisted freedom and their relationship with their school in Vitória/ES. From the narratives of these adolescents, this research seeks to map the processes engendered by the school, its tensions, challenges, inconsistencies, impossibilities and potential. This research is the cartography of agreements and disagreements related to a complex reality woven by these teenagers, their school and the socio-educational measure itself. The narratives and dialogues carried out in the meetings with these adolescents unveil concepts that must be denatured, such as assisted freedom. The reflections evoked by the narrated experiences make the erroneous use of the term "assisted freedom" evident, since this term mirrors a socio-educational measure that produces supervisory practices, control and surveillance. From this analytical perspective, the socio-educational measure of assisted freedom has resulted in an experience of freedom that is centered in the individual himself, rather than in an experience of freedom that is shared by adolescents and adults. The current legislation, notably since the Child and Adolescent Statute, sees adolescents as the bearers of rights, but it does not guarantee the effective reception and integration of adolescents in the world, understood as the man-made home, in the concept of Arendt. The narratives of these adolescents point out to the duty our public policies have to reassess our schools and socio-educational measures from an ethic of responsibility, so that they can set up places and practices that enhance the practice of freedom as a shared experience, an ethic that requests every educator and every adult to think about what they have done in / of the world and that reaffirms the trust in the potential capacity of adolescents to act, rethink and renovate the world.